ANALISIS EFEKTIVITAS MESIN BATCHING PLANT MENGGUNAKAN OVERALL EQUIPMENT EFFECTIVENESS DAN ANALYTICAL HIERARCHY PROCESS - sisiliani, fitria trisna; Sari Wulandari, Indah Apriliana; Sukmono, Tedjo; Marodiyah, Inggit (Metode : Jurnal Teknik Industri, 2024)
In the face of fierce global competition, construction industry companies such as PT XYZ require efficient production machinery to increase productivity. This study aims to evaluate the effectiveness of batching plant machines at PT XYZ using the Overall Equipment Effectiveness (OEE) method and identify improvements through Analytical Hierarchy Process (AHP). The batching plant machine often experiences downtime, especially on line five, which hampers production performance. The OEE method was used to measure three main aspects: availability, performance, and quality, with an average OEE result of 91.34%, which indicates good performance but still below the company's internal standards. Fishbone diagram analysis identified the main causal factors of downtime, while AHP was used to prioritize improvements. The AHP results showed that developing a Standard Operating Procedure (SOP) was the best strategy to reduce downtime, with a weight of 39.8% and consistency of 2%. This research suggests the implementation of SOPs to improve machine effectiveness and maintain optimal productivity at PT XYZ.